Metode Brainstorming Melalui Bimbingan Klasikal Untuk Meningkatkan Motivasi Belajar Siswa Kelas 7E - Tasya Lutfia Tunnisa; Vivi Rahmawati; Nining Solekah (CV. ITTC INDONESIA, 2025)
This study aims to improve the learning motivation of seventh-grade students at SMP Negeri 4 Kediri through the application of the brainstorming method in classical guidance. The Classroom Action Research (CAR) was conducted in two cycles, focusing on students’ participation, confidence in expressing opinions, and group collaboration. The results showed an increase in learning motivation, indicated by more active involvement in discussions, greater willingness to share ideas, and improved teamwork. Allowing students to choose their own groups in the second cycle also proved effective. Thus, brainstorming through classical guidance is proven to enhance students’ learning motivation.